Problems and Perspectives of Using Stem Cells of Cartilage Tissues - Chaikovsky, Yuri B.; Herashchenko, Serhii B.; Deltsova, Olena I. (Problems of Cryobiology and Cryomedicine, 2019)
The paper aims at providing general information regarding the use of stem cells (SCs) for the treatment of cartilage tissue diseases for specialists in the field of biology, cryomedicine and biomechanics. To date, SCs niches have been identified in hyaline cartilage, synovial membranes and synovial fluid of diarthrosis, intervertebral discs, and knee joints menisci, fibrous cartilages of the temporomandibular joint and elastic cartilages of the auricle. Specific features and the mechanism of action of SCs of cartilage tissue were determined. Experimental models of cartilage tissue pathology in different animal species have been developed. Experimental studies have demonstrated the possibility of using SCs for the treatment of diseases caused by cartilage pathology. It is shown that the use of cryopreserved cartilage tissue SCs in medical practice is effective and promising. To date, this issue remains understudied, therefore, it is necessary to develop optimal freezing regimens, select cryoprotective media, as well as evaluate the safety of such a therapy. Â Probl Cryobiol Cryomed 2019; 29(4):Â 303-316